Enhancing Urban Safety And Security. Global Report on Human Settlements 2007 - Lange, Carlos (Revista INVI, 2008)
United Nations Human Settlements Programme (UN-Habitat) Enhancing Urban Safety And Security. Global Report on Human Settlements 2007